Handbook of Upper Extremity Examination A Practical Guide - Pillemer, Roger; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
In addition to complementary radiographic imaging, the physical exam is an essential diagnostic element for the orthopedic surgeon. As such, learning to perform this exam thoroughly is of utmost importance to medical students, residents and interns on an orthopedic rotation and in later practice. This practical text succinctly presents all of the necessary information regarding the physical examination of the upper extremity. The hand, wrist, elbow and shoulder are discussed in dedicated thematic sections, with each section comprised of three main chapters. The initial chapter describes the musculoskeletal anatomy and function of the joint, presenting the tests themselves along with the rationale for performing them. The second chapter presents the systematic examinations carried out in every case, and the third chapter describes examinations for specific conditions relating to the joint, including tendinopathies, osteoarthritis, neurological conditions, deformities, and more. Plentiful bullet points and color images throughout the text describe and illustrate each test and physical sign. Convenient and user-friendly, Handbook of Upper Extremity Examination is a valuable, portable guide to this all-important diagnostic tool for students and practitioners alike.
Part I. Physical Examination of the Hand -- Introduction to the Hand -- Anatomy and Function of the Hand -- A Systematic Examination of the Hand -- Examination for Specific Conditions of the Hand -- Part II. Physical Examination of the Wrist -- Anatomy and Function of the Wrist -- A Systematic Examination of the Wrist -- Examination for Specific Conditions of the Wrist -- Part III. Physical Examination of the Elbow -- Anatomy and Function of the Elbow -- A Systematic Examination of the Elbow and Forearm -- Examination for Specific Conditions of the Elbow -- Part IV. Physical Examination of the Shoulder -- Anatomy and Function of the Shoulder -- A Systematic Examination of the Shoulder -- Examination for Specific Conditions of the Shoulder.
Keywords: Orthopedics; Orthopaedics; Upper Extremity; Physical Examination; Handbook